Avaliação das atividades antifúngica e toxicológica do óleo essencial gaultheria procumbes - Assis, Kivia Sales de (2018)
Candidiasis is an infection caused by yeasts of the genus Candida, whether superficial infections, skin and mucosal or systemic. The spread of drug-resistant fungi is one of the most serious threats to the successful treatment of fungal diseases. Furthermore, some drugs are very toxic, hindering to use therapeutic, which stimulates the search for new, more effective, less toxic antifungal agents. In this context products derived from medicinal plants are excellent alternatives for this purpose. n this sense, the objective of this study was to investigate the antifungal activity of the essential oil of Gaultheria procumbens (OEGp) against strains of the genus Candida, evaluate its cytotoxicity, as well as the oral bioavailability and theoretical toxicological profile of the majority constituent of this oil, salicylate of methyl. To carry out antifungal studies, the microdilution test was used with different fungal strains of the Candida genus to evaluate the Minimum Inhibitory Concentration (MIC) and Minimum Fungicide Concentration (MFC). For the analysis of the antimicrobial potential of salicylate de methyl was used with the in silico analysis software Pass online. To carry out cytotoxic activity studies, human red blood cells were used. The analyzes showed that OEGp showed antifungal activity against clinical strains of C. parapsilosis with MIC and CFM of 8 μg / mL and C. krusei with MIC of 64 μg / mL and CFM of 128 μg / mL, whereas C. tropicalis and C. glabrata were insensitive with except for C. tropicalis LM-64 which had a MIC of 32 μg / ml. OEGp also had antifungal activity against 5 strains of 8 tested C. albicans, with an MIC and CFM between 4 and 8 μg / mL, and this effect had fungicidal action. Its mechanism of action does not involve an effect on the cell wall or plasma membrane. A synergistic effect was observed when combined with amphotericin B (a known clinical antifungal). It showed low cytotoxicity for blood type A and low to moderate for most concentrations tested in different blood types (B and O). Regarding the study of the theoretical pharmacological and toxicological properties of the majority constituent of OEGp, methyl salicylate, it was observed that it was theoretically demonstrated to be a compound that has several possible biological effects on the human body, as well as good bioavailability and low risk of toxicity. Taken together, these results suggest that Gaultheria procumbens essential oil represents a new and promising possibility among products with antifungal activity, especially against strains of C. albicans.